Effectiveness of Using English Module Through Implementation Poster Presentation Aided Vlog To Improve Student Learning Outcomes Information of Students Information System at UPI "YPTK" Padang - rasmita rasmita (Linguistics and ELT Journal, 2019)
This study aims to analyze the effectiveness of the use English modules through the implementation of poster presentations assisted by vlog to improve student learning outcomes in the Information Systems Department at UPI YPTK Computer Science Faculty in Padang. The method used is a mixed method, which combines quantitative and qualitative methods. To achieve the research objectives, the researchers used quasi-experimental design, which involved two groups of participants (control and experimental) in academic year 2017/2018 students majoring in Information Systems, with a purposive sampling technique by taking pre-test, treatment and posttest. The research data were analyzed using the one-sample t-test. The results of the data analysis showed that the pretest and post test scores of the experimental group showed significant differences, while the control group did not show significant differences. This research shows the results that the use of English modules through the implementation of poster presentations assisted by vlog is more effective in improving students’ learning outcomes than those not using the module